ANALISIS KERJA SAMA SANTRI DALAM KEHIDUPAN SEHARI HARI DI PONDOK PESANTREN DARUSSALAM SENGKUBANG - Fadhli, Fahri; Zakso, Amrazi; Rustiyarso, Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research is ?Analysis of Santri Cooperation in Life A Day in Pondok Pesantren Darussalam Sengkubang?. A common problem in this study is how is the cooperation of santri in everyday life in Pondok Pesantren Darussalam Sengkubang, with sub problems (1) how is the cooperation in the form of harmony mutual help santri in Pondok Pesantren Darussalam Sengkubang? (2) how is the cooperation in the form of mutual cooperation harmony santri in Pondok Pesantren Darussalam Sengkubang?. The results of this study (1) form of harmony mutual help santri in Pondok Pesantren Darussalam Sengkubang evidenced by the harmony of the santri in the form of helping in doing daily activities, such as helping with work, help the santri launch Al-Quran reading, help santri to use arabic properly and correctly (2) forms of mutual cooperation together maintain cleanliness Pondok Pesantren Darussalam Sengkubang, together maintain security Pondok Pesantren Darussalam Sengkubang. Keywords: Cooperation, Mutual Cooperation, Mutual Help, Pondok Pesantren Darussalam Sengkubang, Santri